Let $a;b\ge 0$. Prove that inequality $$\frac{2ab}{a+b}+\sqrt{\frac{a^2+b^2}{2}}\ge \sqrt{ab}+\frac{a+b}{2}$$

My try: $LHS-RHS=\frac{2ab}{a+b}-\frac{a+b}{2}+\sqrt{\frac{a^2+b^2}{2}}-\sqrt{ab}\ge 0$

Or $-\frac{\left(a-b\right)^2}{2\left(a+b\right)}+\frac{\left(a-b\right)^2}{2\left(\sqrt{\frac{a^2+b^2}{2}}+\sqrt{ab}\right)}\ge 0$

Or $\left(a-b\right)^2\left(\frac{1}{2\left(\sqrt{\frac{a^2+b^2}{2}}+\sqrt{ab}\right)}-\frac{1}{2\left(a+b\right)}\right)\ge 0$

Then i can't prove $\frac{1}{2\left(\sqrt{\frac{a^2+b^2}{2}}+\sqrt{ab}\right)}\ge \frac{1}{2\left(a+b\right)}$

I squared the two sides of the inequality but the exponential is hard to solve. And I can see $HM+QM\ge AM+GM$ with $n=2$ so is that true for $n=i$?


Note that $$\begin{align}\sqrt{\frac{a^2+b^2}{2}}-\sqrt{ab}&=\frac{\left(\frac{a^2+b^2}{2}\right)-ab}{\sqrt{\frac{a^2+b^2}{2}}+\sqrt{ab}}=\frac{2\left(\frac{a-b}{2}\right)^2}{\sqrt{\frac{a^2+b^2}{2}}+\sqrt{ab}} \end{align}$$ If we can show that $$\sqrt{\frac{a^2+b^2}{2}}+\sqrt{ab}\leq a+b\,,$$ then $$\sqrt{\frac{a^2+b^2}{2}}-\sqrt{ab}\geq \frac{2\left(\frac{a-b}{2}\right)^2}{a+b}=\frac{a+b}{2}-\frac{2ab}{a+b}\,,$$ which is equivalent to what we need to prove.

Note that $$\begin{align} \sqrt{\frac{a^2+b^2}{2}}&=\sqrt{\left(\frac{a+b}{2}\right)^2+\left(\frac{a-b}{2}\right)^2} \\ &=\sqrt{\left(\frac{a+b}{2}\right)^2+\left(\frac{\sqrt{a}-\sqrt{b}}{\sqrt2}\right)^2\,\left(\frac{\sqrt{a}+\sqrt{b}}{\sqrt2}\right)^2} \\ &=\sqrt{\left(\frac{a+b}{2}\right)^2+\left(\frac{\sqrt{a}-\sqrt{b}}{\sqrt2}\right)^2\left(\left(\frac{\sqrt{a}-\sqrt{b}}{\sqrt2}\right)^2+2\sqrt{ab}\right)} \\ &=\sqrt{\left(\frac{a+b}{2}\right)^2+2\sqrt{ab}\left(\frac{\sqrt{a}-\sqrt{b}}{\sqrt2}\right)^2+\left(\frac{\sqrt{a}-\sqrt{b}}{\sqrt2}\right)^4} \\ &\leq\sqrt{\left(\frac{a+b}{2}\right)^2+2\left(\frac{a+b}{2}\right)\left(\frac{\sqrt{a}-\sqrt{b}}{\sqrt2}\right)^2+\left(\frac{\sqrt{a}-\sqrt{b}}{\sqrt2}\right)^4} \\ &=\frac{a+b}{2}+\left(\frac{\sqrt{a}-\sqrt{b}}{\sqrt2}\right)^2\,.\end{align}$$ Thus, $$\sqrt{\frac{a^2+b^2}{2}}+\sqrt{ab}\leq a+b\,.$$

  • $\begingroup$ I think you can use Cauchy-Schwarz's inequality for prove $\sqrt{\frac{a^2+b^2}{2}}+\sqrt{ab}\leq a+b\,.$ it's easy than yours, btw thank you. $\endgroup$ – nDLynk Aug 5 '18 at 11:40
  • $\begingroup$ Unless a Cauchy-Schwarz proof of that inequality is illustrated somewhere, I remain unconvinced. If such a proof doesn't exist, then it is certainly easier than my proof. $\endgroup$ – Batominovski Aug 5 '18 at 11:41
  • 2
    $\begingroup$ By C-S: $\left(\sqrt{\frac{a^2+b^2}{2}}+\sqrt{ab}\right)^2\le 2\left(\frac{a^2+b^2}{2}+ab\right)=\left(a+b\right)^2$ Done :). $\endgroup$ – nDLynk Aug 5 '18 at 11:43
  • $\begingroup$ Good. You can write this as an answer, and I will upvote it. One can answer his own question. $\endgroup$ – Batominovski Aug 5 '18 at 11:44

This Problem is well known. Note that $$\frac{a+b}{2}-\frac{2ab}{a+b}=\frac{(a+b)^2-4ab}{2(a+b)}$$ after squaring two times you will get

$$\left(\frac{(a+b)^2}{2}-\frac{(a-b)^4}{4(a+b)^2}\right)^2\geq 4ab\left(\frac{a^2+b^2}{2}\right)$$ Doing this Algebra you will get

$$\frac{1}{16}\frac{(a-b)^8}{(a+b)^4}\geq 0$$ which is true.

  • $\begingroup$ Thanks Dr.Son now i know your solution. $\endgroup$ – nDLynk Aug 5 '18 at 11:41

An alternative approach, let

$$ u = \frac{a + b}{2} \quad \text{and} \quad v = ab $$

so that the inequality becomes

$$ \frac{v}{u} + \sqrt{2u^2 - v} \ge \sqrt{v} + u. $$

Since the original inequality is homogeneous, and clearly true for $a = b = 0$, we can without loss of generality set $u = 1$. Then letting $v = 1 + x$ reduces the inequality to

$$ x \ge \sqrt{1 + x} - \sqrt{1 - x} \quad (\text{for}\,\, x \le 0) $$

which is shown fairly easily. The condition comes from

$$ u = 1 \implies b = 2 - a \implies x = a(2 - a) - 1 = -(a-1)^2 \le 0. $$

  • $\begingroup$ Nice solutions are written here! $\endgroup$ – Dr. Sonnhard Graubner Aug 5 '18 at 11:49

I think this is the simplest solution:

So you are stuck here:

$$\frac{1}{2\left(\sqrt{\frac{a^2+b^2}{2}}+\sqrt{ab}\right)}\ge \frac{1}{2\left(a+b\right)}$$

...which is equivalent to:

$$\sqrt\frac{a^2+b^2}{2}+\sqrt{ab}\le a+b\tag{1}$$

Apply Jensen inequality:

$$\frac{f(x_1)+...+f(x_n)}{n}\le f(\frac{x_1+...+x_n}{n})$$

...for concave function $f(x)=\sqrt{x}$ and $x_1=\frac{a^2+b^2}{2}$, $x_2=ab$:

$$\frac{\sqrt\frac{a^2+b^2}{2}+\sqrt{ab}}2\le \sqrt{\frac{\frac{a^2+b^2}{2}+ab}{2}}\tag{2}$$

Simplify (2) and you get (1) directly.

  • $\begingroup$ That is a good solution too. $\endgroup$ – nDLynk Aug 5 '18 at 11:48
  • $\begingroup$ Upvote won't hurt :) $\endgroup$ – Oldboy Aug 5 '18 at 11:48
  • $\begingroup$ Sorry but votes cast by those with less than 15 reputation are recorded .-. . $\endgroup$ – nDLynk Aug 5 '18 at 11:50
  • $\begingroup$ @NguyễnDuyLinh As I suggested, posy your own solution as an answer. I will upvote it. Then, you will get more than 15 reputation points. $\endgroup$ – Batominovski Aug 5 '18 at 11:51

Thanks everyone i had the answer for my stuck.

We have : $$LHS-RHS=\frac{2ab}{a+b}-\frac{a+b}{2}+\sqrt{\frac{a^2+b^2}{2}}-\sqrt{ab}\ge 0$$

Or $$-\frac{\left(a-b\right)^2}{2\left(a+b\right)}+\frac{\left(a-b\right)^2}{2\left(\sqrt{\frac{a^2+b^2}{2}}+\sqrt{ab}\right)}\ge 0$$

Or $$\left(a-b\right)^2\left(\frac{1}{2\left(\sqrt{\frac{a^2+b^2}{2}}+\sqrt{ab}\right)}-\frac{1}{2\left(a+b\right)}\right)\ge 0$$

Then i need to prove $$\frac{1}{2\left(\sqrt{\frac{a^2+b^2}{2}}+\sqrt{ab}\right)}\ge \frac{1}{2\left(a+b\right)}$$

Or $\sqrt{\frac{a^2+b^2}{2}}+\sqrt{ab}\leq a+b$. Which's true by C-S $$\left(\sqrt{\frac{a^2+b^2}{2}}+\sqrt{ab}\right)^2\le 2\left(\frac{a^2+b^2}{2}+ab\right)=\left(a+b\right)^2$$

  • 1
    $\begingroup$ This is one of few cases that the OP answered his own question, and quite beautifully. An upvote is very well deserved. $\endgroup$ – Batominovski Aug 5 '18 at 11:55

Let $a^2+b^2=2t^2ab$, where $t>0$.

Thus, by AM-GM $t\geq1$ and we need to prove that $$\frac{2ab}{\sqrt{a^2+b^2+2ab}}+\sqrt{\frac{a^2+b^2}{2}}\geq\sqrt{ab}+\frac{\sqrt{a^2+b^2+2ab}}{2}$$ or $$\sqrt{\frac{2}{t^2+1}}+t\geq1+\sqrt{\frac{t^2+1}{2}}$$ or $$t-1\geq\sqrt{\frac{t^2+1}{2}}-\sqrt{\frac{2}{t^2+1}}$$ or $$t-1\geq\frac{t^2-1}{\sqrt{2(t^2+1)}}$$ or $$\sqrt{2(t^2+1)}\geq t+1,$$ which is true by C-S: $$\sqrt{2(t^2+1)}=\sqrt{(1^2+1^2)(t^2+1)}\geq t+1.$$ Done!


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.